Between‐ and within‐site variability of fMRI localizations. Issue 6 (9th March 2016) - Rath, Jakob; Wurnig, Moritz; Fischmeister, Florian; Klinger, Nicolaus; Höllinger, Ilse; Geißler, Alexander; Aichhorn, Markus; Foki, Thomas; Kronbichler, Martin; Nickel, Janpeter; Siedentopf, Christian; Staffen, Wolfgang; et al.
Abstract: This study provides first data about the spatial variability of fMRI sensorimotor localizations when investigating the same subjects at different fMRI sites. Results are comparable to a previous patient study. We found a median between‐site variability of about 6 mm independent of task (motor or sensory) and experimental standardization (high or low). An intraclass correlation coefficient analysis using data quality measures indicated a major influence of the fMRI site on variability. In accordance with this, within‐site localization variability was considerably lower (about 3 mm). We conclude that the fMRI site is a considerable confound for localization of brain activity. However, when performed by experienced clinical fMRI experts, brain pathology does not seem to have a relevant impact on the reliability of fMRI localizations. Hum Brain Mapp 37:2151–2160, 2016 . ©2016 Wiley Periodicals, Inc.